2020
DOI: 10.1002/num.22547
|View full text |Cite
|
Sign up to set email alerts
|

Finite difference method combined with differential quadrature method for numerical computation of the modified equal width wave equation

Abstract: The aim of this study is to improve the numerical solution of the modified equal width wave equation. For this purpose, finite difference method combined with differential quadrature method with Rubin and Graves linearizing technique has been used. Modified cubic B-spline base functions are used as base function. By the combination of two numerical methods and effective linearizing technique high accurate numerical algorithm is obtained. Three main test problems are solved for various values of the coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 32 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…The newly produced solutions are compared with the existing applications in the literature and their behavior is depicted in graphs. As a result of those comparisons, it can be clearly seen that the proposed algorithm shows the best performance according all previous studies [11,12], [14][15][16][17][18][19], [21][22][23][24][25][26][27][28][29], including those in recent years in the literature. These excellent results are new in terms of accuracy, reliability and cost compared to the results of other applications.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The newly produced solutions are compared with the existing applications in the literature and their behavior is depicted in graphs. As a result of those comparisons, it can be clearly seen that the proposed algorithm shows the best performance according all previous studies [11,12], [14][15][16][17][18][19], [21][22][23][24][25][26][27][28][29], including those in recent years in the literature. These excellent results are new in terms of accuracy, reliability and cost compared to the results of other applications.…”
Section: Discussionmentioning
confidence: 82%
“…Implementation 1.9 In the ninth implementation, to do the comparison with other studies [15], time increment ∆t = 0.1 is utilized. Comparison of the gained results are done with three different variants of the finite difference method and are submitted at [11,12], [14], [16][17][18][19], [21], [22][23][24][25], [28] and [29] in the literature with the new application for time increment ∆t = 0.05 and amplitude c = 0.25. The current error norms are 2.66x10 −7 and 3.19x10 −7 at t = 20.…”
Section: Example I: the Movement Of A Single Solitary Wavementioning
confidence: 99%
See 1 more Smart Citation
“…Bellman et al [39] suggested DQM for approximating of the differential equations. In the past decades, many different base functions have been used for numerical solutions of the differential equations [40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%